2019
DOI: 10.1080/10508422.2019.1645665
|View full text |Cite
|
Sign up to set email alerts
|

Supporting ethical practice in community-engaged research with 4R: Respond, Record, Reflect, and Revise

Abstract: Efforts towards adaptation, dissemination, and implementation of culturally robust, evidenceinformed mental healthcare rely on community-engaged research (CEnR). Academic-community partnerships help bring science to service for vulnerable and historically disenfranchised populations (e.g., communities of color and those characterized by poverty). A growing literature supports the development of a framework of ethics for CEnR. This article examines ethical tensions in the context of the American Psychological A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Additionally, Beaumont & Hollins Martin (2016) propose that Compassionate Mind Training might improve student therapists’ well-being, reduce burnout and compassion fatigue, and promote resilience. Specifically, journaling, reflexivity, and group debriefing (e.g., opportunities to consider events in partnership non-judgmentally as a team, to seek support and guidance) help community-engaged researchers support ethical practice ( Case, 2017 ; Chou & Frazier, 2019 ), consider consultation and partnership with objective distance, and track ongoing work to provide evidence of progress and counter self-critical thinking. Studies also have demonstrated the ability of the Gestalt two-chair technique to increase self-compassion and decrease anxiety and depression ( Neff, 2004 ).…”
Section: Development and Application Of Corementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Beaumont & Hollins Martin (2016) propose that Compassionate Mind Training might improve student therapists’ well-being, reduce burnout and compassion fatigue, and promote resilience. Specifically, journaling, reflexivity, and group debriefing (e.g., opportunities to consider events in partnership non-judgmentally as a team, to seek support and guidance) help community-engaged researchers support ethical practice ( Case, 2017 ; Chou & Frazier, 2019 ), consider consultation and partnership with objective distance, and track ongoing work to provide evidence of progress and counter self-critical thinking. Studies also have demonstrated the ability of the Gestalt two-chair technique to increase self-compassion and decrease anxiety and depression ( Neff, 2004 ).…”
Section: Development and Application Of Corementioning
confidence: 99%
“…Systematic cultivation of ACPs has yielded a robust body of work describing conceptual models to maximize the success of EBP implementation in community-based organizations (CBOs) (see Consolidated Framework for Implementation Research, Damschroder et al, 2009 ), and investigators have presented frontline challenges and examples of problem solving, “lessons learned,” and recommendations for the procedures of ACP ( Frazier et al, 2019 ; Stetler et al, 2006 ). In contrast to the well-established literature describing what to do (e.g., specific steps) in partnership, a growing discourse has increasingly called for guidance in the process of ACP, or how to do it (e.g., ethics, Campbell & Morris, 2017 ; Chou & Frazier, 2019 ). To this end, we introduce Compassion-Oriented Reflection and Engagement (CORE), a process model guiding our role and function as academic partners and describe its development and application through our experience as community-engaged researchers working in collaboration with a youth-serving non-profit organization called Champions (a pseudonym).…”
mentioning
confidence: 99%